OP0283 Increased Neutrophil Extracellular TRAP Formation in Rheumatoid Arthritis is Correlated with the Induction of Pathogenic Th1 And/Or TH17 Cell Responses. (10th June 2014) - Papadaki, G.; Choulaki, C.; Bertsias, G.; Kampas, K.; Repa, A.; Boumpas, D.; Verginis, P.; Sidiropoulos, P.
Abstract : Background: Neutrophils are important in rheumatoid arthritis (RA) pathogenesis, with a key role in inflammation and cartilage damage. Activated neutrophils form extracellular traps (NETs) with potent pro-inflammatory and immunostimulatory activity. Objectives: Thus, we sought to assess the role of NETs in RA pathogenesis using human samples and the collagen induced arthritis (CIA) mouse model. Methods: Human peripheral blood neutrophils were isolated from active RA patients (n=6) and healthy controls (HC) (n=7). NET formation, both spontaneous and following incubation with RA serum (n=7) or synovial fluid (n=7), was assessed by immunofluoresence microscopy (co-staining with myeloperoxidase (MPO) and 4', 6-Diamidino-2-phenylindole dihydrochloride (DAPI)). Extracellular DNA content was quantified by fluorescence spectrometry (picogreen). Bone marrow (BM)-derived neutrophils (Ly6G + ) (from CIA and control mice) were in vitro tested for their ability to form NETs using confocal microscopy (co-staining of extracellular DNA (DAPI) with MPO). Lymph nodes from CIA mice were isolated 9 days after the collagen immunization, cultured in the presence of bovine collagen II (CII) and the presence or absence of CIA-NETs supernatants. IFNγ/IL-17 production in culture supernatants was determined. Results: Freshly isolated RA peripheral blood neutrophils underwent spontaneous NETosis at higher rates compared to healthy controls (p<0.05). Incubation of healthy neutrophils with RA serum or synovial fluid induced higher NET release compared to normal serum (p<0.005). Moreover, RF positive patients (n=6) exhibited significantly increased spontaneous NET formation compared to RF negative (n=8) (p=0.008, DNA quantification by picogreen). In RA mouse model, there was increased NET formation rate in CIA BM neutrophils versus naïve BM neutrophils and the presence of NETs (supernatants from CIA-NETs) significantly augmented the induction of pathogenic Th1 and/or Th17 cell responses compared to supernatants from naïve BM neutrophils (p<0.05). Conclusions: We found that neutrophils from RA patients have enhanced NET formation, driven by soluble factors found in RA sera and synovial fluid, and that the effect was enhanced in seropositive for RF patients. Moreover, there is an evidence for the role of CIA-NETs in the perpetuation of adaptive immune responses. Further studies will address the mechanism through which CIA-NETs enhance the priming of Th1/Th17 immune responses, and whether suppression of NETs in vivo may ameliorate arthritis in RA mouse models. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5315